1998
DOI: 10.1111/j.2044-8279.1998.tb01311.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and education on epistemological beliefs

Abstract: Background. Individuals' beliefs about the nature of knowledge and learning, or epistemological beliefs, have been linked to their comprehension, meta‐comprehension, persistence, and interpretation of information (e.g., Kitchener & King, 1981; Ryan, 1984; Songer & Linn, 1991). Little is known about the development of epistemological beliefs. Aims. This research examines the contributions of age and education to adults' epistemological beliefs. Sample. A total of 418 adults from all walks of life (e.g., homemak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0
39

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(179 citation statements)
references
References 12 publications
7
133
0
39
Order By: Relevance
“…These results seem to be consistent with the related literature (e.g., Wheeler, 2007;Schommer, 1998;Schommer et al, 1997;Jehng et al, 1993). For instance, Schommer (1998) indicated that regression analysis on a large sample of working adults led to the conclusion that more educated participants were less likely to view knowledge as simple or certain. This result seemed not to be surprising because students are expected to be more aware of their own beliefs and cognitive capabilities than younger students (Aydin & Uboz, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results seem to be consistent with the related literature (e.g., Wheeler, 2007;Schommer, 1998;Schommer et al, 1997;Jehng et al, 1993). For instance, Schommer (1998) indicated that regression analysis on a large sample of working adults led to the conclusion that more educated participants were less likely to view knowledge as simple or certain. This result seemed not to be surprising because students are expected to be more aware of their own beliefs and cognitive capabilities than younger students (Aydin & Uboz, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…The relationship between grade level and epistemological beliefs about mathematics has been researched with high school (Schommer et al, 1997), collegiate, (Jehng et al, 1993;Schommer, 1998), and adult (Schommer, 1998) samples. Across all samples studied, the increased level of education was associated with more sophisticated epistemological beliefs.…”
Section: Subgroup Validitymentioning
confidence: 99%
“…A recent study on Finnish third-year bio-science students' epistemological beliefs supports the idea that epistemic beliefs and critical thinking are interconnected, as the students applied critical thinking in order strengthen their thinking in general (Hyytinen, Holma, Toom, Shavelson & Lindblom-Ylänne, 2014). There is also evidence that the more education adults have received, the more probable it is that they will perceive knowledge as complex and constantly in flux (Schommer, 1998). Further, this belief in the complexity and perpetual transformation of knowledge increases the individual's willingness to take multiple perspectives and alter their thinking (Schommer-Aikins & Hutter, 2002).…”
Section: Interconnections Of Critical Thinking and Epistemic Beliefsmentioning
confidence: 91%
“…Admittedly, this will not provide the same detail that individual discourse in the traditional classroom will provide, but it may be sufficient. Students could be surveyed in induction week to provide information, for instance, on their learning styles (Biggs, Kember and Leung, 2001), reflective thinking (Kember et al, 2000;Leung and Kember, 2003), and epistemological beliefs (Clarebout, Elen, Luyten and Bamps, 2002;Schommer, 1990Schommer, , 1998. Students' expectations could also be sought (Maunder and Harrop, 2003).…”
Section: Finding Out More About Studentsmentioning
confidence: 99%